2011
DOI: 10.1007/s00044-011-9586-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of sparfloxacin and commonly used H2 receptor antagonists by RP-HPLC: application to in vitro drug interactions

Abstract: Innovative, simple, economical, and rapid reverse phase HPLC method has been developed and validated for simultaneous determination of sparfloxacin (SPFX) and cimetidine, ranitidine, and famotidine (H 2 receptor antagonists) in bulk material, pharmaceutical formulations, and human serum. Chromatographic system was consisting of schemed HPLC system having UV detector set at 232 nm for cimetidine and, 250 nm for famotidine and ranitidine. Purospher STAR C 18 (250 9 4.6 mm, 5 lm) column was used, and the mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Accuracy and precision of the method were found in acceptable boundary 98.02-102.136% and 0.5-2.2%, respectively. Statistical Paired -test was applied for the verification of the collected data [216]. HPLC simultaneous determination of CIM, RAN, FAM, and NIZ was established using a two-level, full-factorial design with three variables (volume of methanol, percentage of triethylamine, and concentration of phosphate buffer).…”
Section: Simultaneous Determination Of H 2 Receptor Antagonistsmentioning
confidence: 99%
“…Accuracy and precision of the method were found in acceptable boundary 98.02-102.136% and 0.5-2.2%, respectively. Statistical Paired -test was applied for the verification of the collected data [216]. HPLC simultaneous determination of CIM, RAN, FAM, and NIZ was established using a two-level, full-factorial design with three variables (volume of methanol, percentage of triethylamine, and concentration of phosphate buffer).…”
Section: Simultaneous Determination Of H 2 Receptor Antagonistsmentioning
confidence: 99%
“…Many analytical methods have been developed to determine statins, specifically rosuvastatin alone, such as liquid chromatography (Pasha et al ., ), or in combination with other drugs over the past decade as with simvastatin and pravastatin sodium (Chaudhari et al ., ), atorvastatin, lovastatin, pravastatin and simvastatin (Pasha et al ., ), with finofibrate (Sharma and Bhandari, ), with atenolol, spironolactone, glibenclamide and naproxen sodium (Sultana et al ., ), with pioglitazone, gliquidone and simvastatin, with simvastatin, atorvastatin, pravastatin and ceftriaxone (Arayne et al ., ), with diltiazem, atorvastatin and simvastatin (Sultana et al ., ), with lisinopril, pravastatin and atorvastatin (Sultana et al ., ), with captopril, atorvastatin and simvastatin (Sultana et al ., ), with Angiotensin Converting Enzyme (ACE) inhibitors (Arayne et al ., ) and with Non Steroidal Antiinflammatory Drugs (NSAIDs) (Arayne et al ., ; Sultana et al ., ). A number of spectrophotometric and RP‐HPLC methods have been reported for the quantitative determination of fluoroquinolones in pharmaceutical formulations and spiked human serum (Joshi, ; Belal et al ., ; Santoro et al ., ; Arayne et al ., ; Sultana et al ., ) as well as simultaneous determination of quinolones with other co‐administered drugs (Gul et al ., ; Sultana et al ., ,,, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods for the simultaneous determination of coadminstered drugs have also been reported by our research group as simultaneous determination of rosuvastatin, lisinopril, captopril and enalapril [19], lisinopril, [20] verapamil [21], captopril [22], ceftriaxone sodium [23], diltiazem [24] rosuvastatin [25] and sparfloxacin [26] with NSAIDs in API, pharmaceutical formulations and human serum by RP-HPLC. Arayne et al [27][28][29][30][31][32][33][34] and Sultana et al [35][36][37][38][39][40] have previously reported, a number of methods for drug-drug interaction studies using UV-visible spectroscopic and RP-HPLC. In continuation of this work we have attempted to study in vitro interactions of leflunomide with flurbiprofen, ibuprofen, diclofenac sodium and mefenamic acid (Figure 1), the experiment was accomplished by the use of UV-visible spectroscopic and RP-HPLC techniques.…”
Section: Introductionmentioning
confidence: 99%